(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Each country has its own specific requirements with regard to the visual standards applicable to drivers. The following were summarised in the appropriate tables: 1) data contained in the Ordinance of the Minister of Health from the 30th of August 2019 regarding medical examinations of applicants for driving licences and drivers; 2) Directive 2006/126/EC of the European Parliament and the Council on driving licences updated on the 22nd of July 2018; 3) the government and nonprofit websites: Advice for Medical Professionals to Follow when Assessing Drivers with Visual Disorders updated on the 4th of March 2020. Both in Poland and the UK the required visual acuity of car and motorcycle drivers is 0.5, which is in line with the EU recommendations. The visual field of both eyes for car and motorcycle drivers with limit values horizontal ≥ 120°, range ≥ 50° right and left and ≥ 20° up and down is identical in Poland and the UK and coincides with the EU recommendations. Colour vision for drivers in the UK is not required, which is consistent with the EU recommendations, whereas in Poland, car and motorcycle drivers do not have to recognise colours, but bus and lorry drivers must correctly recognise red, green and yellow. Current minimum visual requirements for drivers in Poland are closely integrated with the EU recommendations and are similar to the criteria in the UK. They are not too strict but are sufficient to maintain safe driving and there is still a possibility of their liberalization.